FUNGSI SERIKAT BURUH DALAM MENYELESAIKAN PERSELISIHAN HUBUNGAN KERJA TERKAIT PESANGON PEKERJA PADA T. INDAH LOGISTIK - Khairun Nisa; Rika Lestari; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Trade union is an organization formed of, by, and for workers / laborers, both in the Company and outside the Company, which is free, open, independent, democratic, and responsible to fight, defend, and protect the rights and interests of workers / laborers and to improve the welfare of workers / laborers and their families. In the case of not maximal function Prosperity Trade Union Federation in resolving the dispute with PT. Indah logistics related to labor relations disputes related to severance of workers which led to the dispute becomes protracted.The purpose of this research is to know how the function of trade unions in resolving labor disputes related to severance of workers at PT. Indah logistics, to determine the resistance of trade unions in resolving labor disputes related to severance of workers at PT. Indah Logistics, to know how the efforts made by trade unions to overcome obstacles in resolving labor disputes related to severance of workers at PT. Indah Logistics.Keywords: Trade Unions - Termination – Severance